Demonstration of transoral surgery in cadaveric specimens with the medrobotics flex system. (14th March 2013) - Johnson, Paul J.; Serrano, Carlos M. Rivera; Castro, Michael; Kuenzler, Richard; Choset, Howie; Tully, Stephen; Duvvuri, Umamaheswar
<x xml:space="preserve">Abstract</x> Objectives/Hypothesis Using human cadavers, we investigated the feasibility of using a new robotic platform, the Medrobotics Flex System, for laryngeal access and flexible tool delivery to facilitate the performance of pharyngolaryngeal procedures without laryngeal suspension. Our initial trials specifically assess the utility of this experimental robotic system for epiglottectomy and base of tongue resection. Study Design Feasibility; Level of evidence: NA. Methods Using standard mouth retractors, the Flex™robot was driven via the physician controller to the supraglottic region. Non‐crossing, flexible endoscopic tools were inserted through the robot's external tool channels to retract, cauterize, and remove tissue in each procedure type. Mock surgical procedures were performed on the laryngopharyngeal complex including epiglottectomy, base of tongue resection, and vocal cord excision. Time‐to‐tissue exposure was noted for each procedure. Each epiglottectomy was timed to determine operation duration. Results Epiglottectomy, base of tongue resection, and vocal cord excision were successfully performed without suspension laryngoscopy. Individual surgeons improved the procedure time significantly (P = 0.03) between first and second attempts. Epiglottectomies were performed in an average time of 42 minutes (N = 5, σ = 28 minutes). Conclusions The Medrobotics Flex System demonstrates great potential as a surgical tool in head and neck oncology. Compared to other surgical robots, the Flex System offers facilitated access, vision, and triangulation of flexible tools for procedures in the endolarynx. Level of Evidence N/A